Hubungan antara Bauran Pemasaran dengan Penerimaan dari Tanaman Hias di Kota Kendari - Syahroni, Syahroni; Surni, Surni; Dirgantoro, Muhammad Arief (Department of Agribusiness, Halu Oleo University, 2019)
This research was motivated by the marketing of ornamental plants in Kendari City which faced several problems, namely the physical properties of perishable and bulky agriculture products, thus reducing their value and quality. Therefore, in marketing ornamental, traders can apply a marketing mix (product, price, place, and promotion) that can be controlled to achieve marketing goals in meeting their target market. The research objective was to examine the relationship between the marketing mix and the revenue of ornamental plants in Kendari City. Data analysis using spearman correlation analysis. The result showed the relationship between each marketing mix with revenue from ornamental plants, each valued a) product = 0,625 (level of strong relationship), b) price = 0,667 (level of strong relationship), c) place = 0,586 (level of moderate relationship), d) promotion = 0,011 (very low level of relationship).